OA in 2011: age-related OA : a concept emerging from infancy? - Aigner, Thomas; Richter, Wiltrud (Nature reviews. Rheumatology, 2012)
That primary osteoarthritis (OA) is an age-related disorder is undoubted, but how aging contributes to OA is poorly understood. New insights from 2011 offer potential explanations, novel models for study, and the suggestion that a deeper understanding of what 'aging' actually is might pave the way to everlasting joints.